Mobile medical simulation for rural anesthesia providers: A feasibility study - Premkumar, Kalyani; Umaefulam, Valerie; O'Brien, Jennifer (Canadian Medical Education Journal, 2020)
Introduction: Family practice anesthesia (FPA) providers are family physicians trained to deliver anesthesia care; they often practice in rural hospitals to facilitate surgical care. FPA providers in rural hospitals face challenges including professional isolation and limited opportunities for formal continuing education. To address needs identified by FPA providers, we piloted mobile medical simulation in rural Saskatchewan. Methods: Using a logic model framework, we evaluated feasibility of a one-day interdisciplinary mobile simulation workshop for healthcare providers in a rural Saskatchewan hospital. As part of this mixed methods pilot study, we interviewed stakeholders to explore their perceptions of human and financial resources associated with delivering medical simulations in rural locations. Multiple simulation scenarios were utilized to train participants in clinical and professional skills. Participants completed pre- and post-workshop surveys to evaluate their experience. Results: Financial and human resources included cost of renting, transportation of mannequins, and the time required to create the scenarios. Participants (n = 10) reported improved knowledge and found the experience valuable. The session prompted participants to reflect on their deficiencies in certain clinical procedures/skills and highlight learning strategies to address the gap. Discussion: Mobile medical simulation brought continuing medical education (CME) to health professionals in a rural location, but the program was expensive. Our logic model may inform educators and administrators considering mobile medical simulation for physicians in rural areas when balancing resource allocation and the organization’s commitment to CME for rural physicians.